Pendidikan Islam dalam Konsep Prophetic Intelligence - Hayat (Jurnal Pendidikan Islam, 2013)
Intelligence has connectivity to the educational process as a concrete step in the development of human character as a caliph in the world to think of all God ‘s creation. Islamic education teaches a life of meaning to the concept of “Amar ma’ruf nahi mungkar”. It is really clear that various concepts in Islamic education are not adjusted enough with the development period that is increasingly sophisticated and globalized. Islamic civilization has been built since the Prophet Muhammad SAW, and other thinkers in teaching a sense of knowledge that is based on Al- Quran and Al - Hadits as the main guideline. Prophetic Intelligence provides an illustration that in transforming education through the concrete steps for being “Insan Kamil” that is “rahmatan Lil Alamin”. Intelligence Prophetic provides illustration that in transforming education through the concrete steps for being ‘Insan Kamil’ that is ‘rahmatan Lil Alamin’.